Analisis Strategi Pemasaran dan Inovasi Produk Mochica dengan Menggunakan Medsos (Tiktok) dalam Meningkatkan Penjualan - Roswati, Ade Bila; Sugiharto, Muhammad (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
Mochica is one of the MSMEs in West Bandung Regency and is also a leading product in Situ Ciburuy. The reason the author is interested in conducting research is because the researcher is interested in the marketing strategy and innovation of Mochica products in order to increase sales to online media (TikTok) which has much wider potential. Where the growth is less than my expectations, so information about the Mochica product is further expanded by using media on the TikTok application using an empirical approach. This research is descriptive qualitative, because this research is a study to reveal previously existing facts into a study that focuses on efforts to reveal problems and conditions, as they are, which are researched and studied as something whole. This research is descriptive research, because the data collected is in the form of words, pictures, and not numbers. The process of carrying out this qualitative research involves several important efforts, by asking several questions and procedures, collecting specific data, analyzing data empirically and the final report for this research has a flexible structure or framework. Mochica already has and implements its marketing strategy. The marketing strategy is through media (TikTok) and is analyzed based on (seven) variables in the 7P marketing mix.